Prognostic value of CT-derived left atrial and left ventricular measures in patients with acute chest pain. Issue 86 (January 2017) - Takx, Richard A.P.; Vliegenthart, Rozemarijn; Schoepf, U. Joseph; Nance, John W.; Bamberg, Fabian; Abro, Joseph A.; Carr, Christine M.; Litwin, Sheldon E.; Apfaltrer, Paul
Highlights: LV mass and LA diameter are independent prognostic factor for composite MACE. LV mass and LA diameter were not significant prognostic factors for MACE in African Americans. Assessment of LV mass by CT may have a role in the management of patients. Abstract: Purpose: To determine which left atrial (LA) and left ventricular (LV) parameters are associated with future major adverse cardiac event (MACE) and whether these measurements have independent prognostic value beyond risk factors and computed tomography (CT)-derived coronary artery disease measures. Materials and methods: This retrospective analysis was performed under an IRB waiver and in HIPAA compliance. Subjects underwent coronary CT angiography (CCTA) using a dual-source CT system for acute chest pain evaluation. LV mass, LV ejection fraction (EF), LV end-systolic volume (ESV) and LV end-diastolic volume (EDV), LA ESV and LA diameter, septal wall thickness and cardiac chamber diameters were measured. MACE was defined as cardiac death, non-fatal myocardial infarction, unstable angina, or late revascularization. The association between cardiac CT measures and the occurrence of MACE was quantified using Cox proportional hazard analysis. Results: 225 subjects (age, 56.2 ± 11.2; 140 males) were analyzed, of whom 42 (18.7%) experienced a MACE during a median follow-up of 13 months. LA diameter (HR:1.07, 95%CI:1.01–1.13 per mm) and LV mass (HR:1.05, 95%CI:1.00–1.10 per g) remained significant prognostic factor of MACE after controlling for Framingham risk score. LA diameter and LV mass were also found to have prognostic value independent of each other. The other morphologic and functional cardiac measures were no significant prognostic factors for MACE. Conclusion: CT-derived LA diameter and LV mass are associated with future MACE in patients undergoing evaluation for chest pain, and portend independent prognostic value beyond traditional risk factors, coronary calcium score, and obstructive coronary artery disease.